Visualizing the In Vivo Dynamics of Anti-Leishmania Immunity: Discoveries and Challenges - Zayats, Romaniya; Uzonna, Jude E.; Murooka, Thomas T. (Frontiers in Immunology, 2021)
Intravital microscopy, such as 2-photon microscopy, is now a mainstay in immunological research to visually characterize immune cell dynamics during homeostasis and pathogen infections. This approach has been especially beneficial in describing the complex process of host immune responses to parasitic infections in vivo, such as Leishmania. Human-parasite co-evolution have endowed parasites with multiple strategies to subvert host immunity in order to establish chronic infections and ensure human-to-human transmission. While much focus has been placed on viral and bacterial infections, intravital microscopy studies during parasitic infections have been comparatively sparse. In this review, we will discuss how in vivo microscopy has provided important insights into the generation of innate and adaptive immunity in various organs during parasitic infections, with a primary focus on Leishmania. We highlight how microscopy-based approaches may be key to providing mechanistic insights into Leishmania persistence in vivo and to devise strategies for better parasite control.